The Premature Ejaculation Diagnostic Tool (PEDT): Linguistic Validity of the Chinese Version. (25th June 2014) - Huang, Yan‐Ping; Chen, Bin; Ping, Ping; Wang, Hong‐Xiang; Hu, Kai; Zhang, Tao; Yang, Hao; Jin, Yan; Yang, Qi; Huang, Yi‐Ran
Abstract Introduction The premature ejaculation diagnostic tool (PEDT) was developed to standardize the diagnosis of PE and has been applied in many countries. However, a linguistic validation of the Chinese version of PEDT does not exist. Aims This study aims to undertake the Chinese validation of the PEDT and to evaluate its association with self‐estimated intravaginal ejaculatory latency time (IELT) and clinical expert diagnosis of PE. Methods A Chinese version of PEDT was confirmed by andrologist and bilingual linguist. Participants were recruited among seven different communities of Shanghai from 2011 to 2012, and their information regarding self‐reported PE, self‐estimated IELT, expert diagnosis of PE, and PEDT scores were collected. Main Outcome Measures Validity of the PEDT and its association with clinical expert diagnosis of PE and self‐estimated IELT were analyzed. Results A total of 143 patients without PE (mean age 55.11 ± 7.65 years) and 100 men with PE (mean age 53.07 ± 8.08 years) were enrolled for validation. Of the patients in PE group, the number of men reporting self‐estimated IELTs of ≤1, 1–2, and >2 minutes were 34 (34.0%), 22 (22.0%), and 44 (44.0%), respectively. The Cronbach's alpha score (α = 0.77) showed adequate internal consistency, and the test–retest correlation coefficients of each item (r ≥ 0.70, P < 0.001) indicated excellent stability over time. The frequency of agreement showed that there was excellent concordance between PEDT diagnosis and clinician diagnosis when the PEDT scores ≥11. An adequate correlation was found between total PEDT score and self‐estimated IELT (ρ = −0.396, P < 0.001), and sensitivity and specificity analyses suggested a score of ≤8 indicated no time‐defined PE (self‐estimated IELT ≤1 minute). Conclusions The Chinese version of PEDT is valid in screening the presence of PE among Chinese men. The PEDT showed an adequate negative correlation with self‐estimated IELT and an excellent concordance with clinician diagnosis of PE. Huang Y‐P, Chen B, Ping P, Wang H‐X, Hu K, Zhang T, Yang H, Jin Y, Yang Q, and Huang Y‐R. The premature ejaculation diagnostic tool (PEDT): Linguistic validity of the Chinese version. J Sex Med 2014;11:2232‐2238.